Genistein‐3′‐sodium sulphonate protects against lipopolysaccharide‐induced lung vascular endothelial cell apoptosis and acute lung injury via BCL‐2 signalling. Issue 1 (22nd November 2019) - Yi, Lei; Chang, Mengling; Zhao, Quanming; Zhou, Zengding; Huang, Xiaoqin; Guo, Feng; Huan, Jingning
Abstract: Under septic conditions, Lipopolysaccharide (LPS)‐induced apoptosis of lung vascular endothelial cells (ECs) triggers and aggravates acute lung injury (ALI), which so far has no effective therapeutic options. Genistein‐3′‐sodium sulphonate (GSS) is a derivative of native soy isoflavone, which has neuro‐protective effects through its anti‐apoptotic property. However, whether GSS protects against sepsis‐induced lung vascular endothelial cell apoptosis and ALI has not been determined. In this study, we found that LPS‐induced Myd88/NF‐κB/BCL‐2 signalling pathway activation and subsequent EC apoptosis were effectively down‐regulated by GSS in vitro. Furthermore, GSS not only reversed the sepsis‐induced BCL‐2 changes in expression in mouse lungs but also blocked sepsis‐associated lung vascular barrier disruption and ALI in vivo. Taken together, our results demonstrated that GSS might be a promising candidate for sepsis‐induced ALI via its regulating effects on Myd88/NF‐κB/BCL‐2 signalling in lung ECs.